The Value of Expert Opinion in the Pricing of Bordeaux Wine Futures*. (1st August 2016) - Ashton, Robert H.
Abstract: The value of expert opinion for establishing prices in the Bordeaux futures market is analyzed. The expert opinions examined are the wine quality ratings provided by two of the world's foremost wine experts, Robert Parker and Jancis Robinson, for more than 1, 700 red Bordeaux wines over the period 2004–2012. The results show that the experts' ratings have both a statistically and practically significant impact on prices after controlling for the effects of other known determinants of price. Thus, expert opinion has significant value in this setting. The results further show that although Parker's impact on prices is significantly greater than Robinson's, combining the quality ratings of both experts has a significantly greater impact than Parker's ratings alone. As hypothesized, the strength of the results differs for wines produced in different regions of Bordeaux because of differences in the availability of other quality-related information. All results are robust to several alternative sample specifications and other research design choices. (JEL Classifications: C52, G13, L11, L15, M21)